Media Framing and Public Education Analysis: The Indonesian Ministry of Finance’s Crisis Communication Strategy in the Diaper and Wet Wipe Excise Issue - Nadya, Anzakyel Izdihar (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The proposed plan to impose excise taxes on disposable diapers and wet wipes triggered strong public reactions after several media outlets, particularly Tempo, framed the issue as a potential financial burden on households and a strategy to boost state revenue. This framing heightened public sensitivity, especially among mothers and lower-income families. This study analyzes the Ministry of Finance’s response strategy through media framing analysis and crisis communication using secondary data from news reports and official statements. The findings show that the Ministry adopted diminish and instructing information strategies, emphasizing that the excise plan remains in an early policy review stage and will not be implemented soon. The prompt response helped contain the issue and redirect the public narrative toward the ongoing policy assessment.